The myth of the nuclear revolution power politics in the atomic age - Lieber, Keir A. (Keir Alexander), 1970-; Press, Daryl Grayson (Cornell studies in security affairs., 2020)
"Explains the intensity of international competition in the nuclear age and the main deterrence challenges of the twenty-first century"--